MENJAGA HAK PILIH MASYARAKAT PADA PEMILU 2024 MELALUI WEBSITE SIDALIH - Putra, Anak Agung Gede Angga Baskara; Putri, Putu Indah Dianti (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
The Tridharma of Higher Education regulates universities to solve problems in society, including through community service activities. Thematic Community Service Program (KKN) this time is a community service model that focuses on the preparation and implementation of the 2024 General Election in Padangsambian Klod Village. KKN places students in the community to work together with the village PPS to make the 2024 Election a success by going directly to the community in the banjars of each hamlet in the village. Students can synergize and implement the science they study with community life, train care, leadership, cooperation, value order, and community norms. Thematic KKN this time is related to organizing quality, transparent, and accountable elections. The author has an effort to improve the quality and transparency of elections by utilizing information technology. The Voter Data Information System (Sidalih) is one of the solutions introduced to help manage voter data digitally. Thus, it is expected that voter data management can be done more structurally and efficiently. Students involved in this work program bring information technology skills and the spirit to contribute to improving the quality of election administration at the village level. Through the utilization of information technology, the democratic process at the local level can be improved.